Determinants of burnout among nurses and midwives at a tertiary hospital in Ghana: A cross‐sectional study - Douglas Aninng Opoku; Nana Kwame Ayisi‐Boateng; Aliyu Mohammed; Alhassan Sulemana; Abigail Owusuwaa Gyamfi; Dominic Kwabena Owusu; Dorothy Yeboah; Kathryn Spangenberg; Hilda Maria Ofosu; Anthony Kwaku Edusei (Wiley, 2023)
Abstract Aim This study determined the prevalence and key determinants of burnout among nurses and midwives in Kumasi, Ghana. Design Hospital‐based cross‐sectional study. Method A questionnaire was used to obtain data from 391 nurses and midwives at a tertiary hospital in Kumasi, Ghana using simple random sampling. Results About 84.4% of the participants were females. The majority of the study participants experienced low burnout for all dimensions (58% in emotional exhaustion, 55.5% poor personal accomplishment and 38.3% depersonalization). Multiple regression analysis revealed that high emotional exhaustion was independently predicted by post‐graduate education (β = 6.42, p = .003), lack of support from management (β = 2.07, p = .024), dislike for leadership style, (β = 3.54, p < .001) and inadequate number of staff (β = 2.93, p = .005). Age (β = 0.35, p = .004), lack of support from management (β = 1.60, p = .012), and inadequate number of staff (β = 1.49, p = .034) independently predicted high depersonalisation. Female sex (β = 4.36, p < .001) and years of practice (β = −0.26, p < .001) independently predicted low personal accomplishment.